Adapting information and communication technologies for effective education - Tomei, Lawrence A. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book addresses ICT assessment in universities, student satisfaction in management information system programs, factors that impact the successful implementation of a laptop program, student learning and electronic portfolios, and strategic planning for e-learning. It provides innovative research on several fundamental technology-based initiatives, and will make a valuable addition to every reference library"--Provided by publisher.